Leadership Strategies of Elementary School Principals in Developing Teacher Professionalism - Irdayanti Mat Nasir; Nunuk Hariyati; Suyud Suyud; Diani Fitriana Susmita; Dwi Esti Andriani (Universitas Negeri Yogyakarta, 2020)
Principal leadership plays a vital role in school effectiveness through its direct effect on teachers. This study aimed to explore the leadership strategies performed by school principals to develop teacher professionalism at elementary schools. The theoretical underpinnings of interpretivism guided this study. It employed in-depth semi-structured interviews and document analysis to collect data. The interviews were conducted with nine elementary school principals in Klaten district, Indonesia. Data were analyzed using the grounded theory data analysis method, specifically the use of constant comparison through open coding. The 'open-coded' data were then analyzed using the analytic induction technique. The results show that the principals employ a wide range of leadership strategies to develop teacher professionalism. The strategies include providing exemplary behavior and attitude, fostering work discipline, motivating teachers, providing educational supervision, and encouraging teachers to participate in continuing professional development programs.